REGULASI PEMERINTAH DALAM KEAMANAN PENYELENGGARAAN PERDAGANGAN CRYPTO ASSET SEBAGAI INSTRUMEN INVESTASI DIGITAL - Raya, Muhammad Yaasiin (Jurusan Hukum Ekonomi Syariah Fakultas Syariah dan Hukum Uin Alauddin Makassar, 2022)
Abstract Cryptocurrency is a digital currency system where users use digital payments for business activities carried out which function as standard currency. The type of research in this paper is legal research, namely finding the truth of coherence, whether the rule of law is in accordance with legal norms and whether there are norms in the form of orders or prohibitions that are in accordance with legal principles, and whether a person's actions are in accordance with legal norms (not just according to legal rules). or legal principles. Government regulations regarding Crypto Asset are regulated in laws and regulations. In an effort to control and maintain the security of Crypto Asset trading, it is regulated in Bappebti Regulation No. 5 of 2019 and its amendments. To guarantee legal certainty and protection for Cryptocurrency investors, as a form of legal protection for Cryptocurrency investors, all Cryptocurrency marketplaces must fulfill all the requirements set out in Bappebti rules by collecting all requested files, prioritizing the principles of proper business management, such as prioritizing the rights of futures exchange members to obtain open value and ensure that consumers remain protected. Keywords: Crypto Asset, Digital Investment, Regulation, Security, Trading.